2006
DOI: 10.1111/j.1365-2133.2006.07354.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of psoriasis guidelines on appropriateness of referral from primary to secondary care: a randomized controlled trial

Abstract: Dissemination of guidelines on the management of psoriasis in primary care can significantly enhance the appropriateness of referral of patients to secondary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 15 publications
(21 reference statements)
0
23
0
Order By: Relevance
“…1 Therefore, how well ostomy patients adapt to their new life depends, to a great extent, on the preservation of peristomal skin integrity. 6,7 Assessment of disease severity is an integral part of any diagnostic and therapeutic decision. Skin disorders are recognized in dermatology and most often classified as simple inflammatory skin disorders related to mechanical, chemical, infectious, underlying disease or allergic factors.…”
Section: Discussionmentioning
confidence: 99%
“…1 Therefore, how well ostomy patients adapt to their new life depends, to a great extent, on the preservation of peristomal skin integrity. 6,7 Assessment of disease severity is an integral part of any diagnostic and therapeutic decision. Skin disorders are recognized in dermatology and most often classified as simple inflammatory skin disorders related to mechanical, chemical, infectious, underlying disease or allergic factors.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients with chronic plaque psoriasis have mild to moderate disease that is amenable to treatment with topical therapies in primary care . Nevertheless, the level of adherence to topical regimes for those with psoriasis has been found to be low.…”
Section: Introductionmentioning
confidence: 99%
“…'s paper is timely, since there is a paucity of studies which has examined the effect of practice guidelines on the management of psoriasis. As the authors note, two of the most prominent studies have shown discrepant results [161,162], an outcome due possibly to suboptimal guideline dissemination and/or a lack of supporting educational interventions designed to encourage guideline use [160]. In analysing the results of their study, Nast et al.…”
Section: Part Ii: Clinical Attitudes To and Understanding Of Ebm And mentioning
confidence: 99%